Identifying conducive contexts and working mechanisms of sedentary behaviour interventions in older adults: a realist review protocol as part of the ‘Stand UP Seniors’ project - Sebastien F M Chastin; Greet Cardon; Sofie Compernolle; Delfien Van Dyck; Kenneth Vanhove; Emelien Lauwerier (BMJ Open)
Introduction Lifestyle behaviours, including sedentary behaviour, have been listed as key modifiable factors to promote healthy ageing. Sedentary behaviour is ubiquitous in older adults and has a strong link with age-related functional declines and chronic health conditions. Although several interventions have been developed aimed at the reduction of sedentary behaviour in older adults, little in-depth information is available on how these complex interventions work in different contexts. Therefore, the aim of our study was to unpack the mechanisms of how existing interventions aimed at the reduction of older adults’ sedentary behaviour work or fail to work in particular contexts in order to optimise the development and implementation of future sedentary behaviour interventions.Methods and analysis A realist review will be conducted as a first part of the Stand UP Seniors (SUPS) project and will be structured as follows: (1) defining the scope of the review, (2) searching and appraising the evidence, (3) extracting data and synthesising the results, and (4) drawing conclusions and formulating recommendations. The result of this iterative process will be a final programme theory that can be used to identify which context triggers which mechanism, and in turn might elicit which outcome. The final programme theory will be used to inform the second and the third parts of the SUPS project, which are, respectively, the development and evaluation of a sedentary behaviour intervention in older adults.Ethics and dissemination Ethical approval is not required for the review. Dissemination of the realist review results, including the final programme theory, will occur through peer-reviewed publications and presentations at relevant conferences. The peer-reviewed realist review will be prepared according to the Realist and Meta-narrative Evidence Synthesis: Evolving Standards publication standards for realist syntheses.PROSPERO registration number CRD42021248795.